Implementasi Metode Pembelajaran Kooperatif Snowball Throwing Untuk Meningkatkan Keaktifan Belajar - Rahayu, Dila Fuji; Jamal, Moh. Yusup Saepuloh (Prodi PAI IAILM Suryalaya, 2024)
This study aims to determine the activeness of students before applying the snowball throwing cooperative learning method to SKI subjects at MTs Al-Munawwarah, to know the activeness of students after applying the snowball throwing cooperative learning method to SKI subjects at MTs Al-Munawwarah, and to know the differences before and after applying the snowball throwing cooperative learning method to SKI subjects at MTs Al-Munawwarah. This type of research is an experiment with the research design used, namely one group pre test-post test design. The population of this study was students of grade VIII MTs Al-Munawwarah, Cikarag Village, Malangbong District, Garut Regency. With a class VIII-A sample of 25 people. Data collection techniques use observation, tests and interviews. Based on the test results to 25 respondents, the study showed that the test results before applying the snowball throwing cooperative learning method to the SKI subjects at MTs Al-Munawwarah got an average count of 40.7 was on sufficient clarification. Meanwhile, the test results after applying the snowball throwing cooperative learning method to the SKI subject at MTs Al-Munawwarah got an average count of 62.4 which was on good clarification. Thus, there is a difference in the learning activity of students before applying the snowball throwing cooperative learning method with after applying the snowball throwing cooperative learning method in SKI subjects at MTs Al-Munawwarah, this is evidenced by the calculation of tcalculate obtaining 11,88 and ttabel obtaining 9.21 it is proven that χ²calculate > χ²table = 11,88 > 9.21. The research is more valid by making observations and direct interviews with SKI teachers at MTs Al-Munawwarah that the application of the snowball throwing cooperative learning method can increase the activeness of students at MTs Al-Munawwarah, Cikarag Village, Malangbong District, Garut Regency.